GE_GERICHTE C/4055/2017 vom 18. September 2018 - GE Cour de justice (2018)
PROTECTION DE L'UNION CONJUGALE ; OBLIGATION D'ENTRETIEN ; CONJOINT ; ENFANT ; REVENU HYPOTHÉTIQUE | CC.276.leta.ch1; CC.276; CC.328